Recurrent deep vein thrombosis in children with malignant blood diseases: literature review - D. S. Morozova; D. A. Evstratov; P. A. Zharkov (Онкогематология, 2019)
Venous thromboembolism is not a rare complication in children with cancer. Despite the advantages of the treatment of venous thromboembolism there is still a probability of venous thromboembolism recurrence. In adult patients with cancer venous thromboembolism recurrence an influence on the lower survival rate. In children with cancer venous thromboembolism recurrence is a rare complication, but it can significantly reduce the quality of life. Risk factors of venous thromboembolism recurrence in children with cancer are not properly investigated.